Expanding ISAF - ending OEF: The debate on the mandates sending German troops to Afghanistan - Markus Kaim (Stiftung Wissenschaft und Politik (SWP), 2007)
The present debate on the renewal of the three mandates dispatching German troops to Afghanistan reveals the public's increasing difficulty to comprehend why the Bundeswehr, Germany's Federal Armed Forces, are currently operating under three different mandates in the same country - each with different objectives, a different scope of action, and tied into different command structures. To ensure that the operations in Afghanistan succeed, it is thus imperative that these three missions be rolled into a single coherent mandate to the International Security Assistance Force (ISAF), and that the German mandate to Operation Enduring Freedom (OEF) be allowed to lapse, which would garner the necessary domestic support for the mission and also enable Germany to live up to its duties as a NATO ally. At the same time, the German federal government should press its other allies to end the OEF in Afghanistan and place all their troops under ISAF command. This quantitative expansion of the ISAF mission could then pave the way for a more equitable transatlantic distribution of the burden in Afghanistan
Keywords: 320